Modelling of Rheological Properties of Mango (cv. Neelum) Suspensions: Effect of Sample Concentration and Particle Size - Mahawar, Manoj Kumar; Jalgaonkar, Kirti; Nambi, V. Eyarkai; Bibwe, Bhushan; Thirupathi, V. (Journal of Agricultural Engineering, 2019)
Evaluation of rheological properties of reconstituted mango peel powder (MPP) cv. Neelum at different particle sizes and sample concentrations was investigated. The combined effect of sample (MPP: water) concentration (1:4, 1:5, 1:6) and particle size obtained from sieve openings (420 μm, 355 μm, 250 μm and 125 μm) were evaluated on the rheological parameters (yield stress, flow behaviour index and consistency index). Lightness (L) and yellowness (b) increased while greenness (a) decreased with reduction in particle size. The increase in sample concentration was associated with increase in shear stress values.Rheological characterization was performed on the basis of coefficient of determination (R2) and other model parameters. For the samples (particle size of 250μm and 125μm), the Herschel-Bulkey model (R2≥0.831), Power law (R2≥0.803) and Casson law (R2≥0.832) fitted well to shear stress-shear rate data.